DSC investigation of the influence of human placenta fractions on the thermal stability of protein complexes of erythrocyte membranes - Govorova, Yu.S.; Zinchenko, O.V.; Semenchenko, O.Yu.; Bobrova, O.M.; Nardid E.О.; Nardid , O.A. (Reports of the National Academy of Sciences of Ukraine, 2018)
The effect of placenta extracts fractions on the thermal denaturation of erythrocyte membrane-bound proteins is investigated by differential adiabatic scanning calorimetry. Four transitions are registrated on a denaturation thermogram of white erythrocyte ghosts. Adding the placenta extracts fractions to the suspension of erythrocyte membrane-bound proteins leads to increasing the temperature of all protein groups except spectrin.